Perilaku Tokoh Protagonis dan Antagonis pada Naskah Drama ”Bila Malam Bertambah Malam” Karya Putu Wijaya - Apadu, Rahman; Arsadi, Nurlena; Bagtayan, Zilfa Achmad (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
Drama script is a text that contains dialogue with descriptions of the characters in it. This study aims to describe (a) the behavior of the protagonist (b) the behavior of the antagonist and (c) its implications in learning literature in schools. A descriptive qualitative approach is utilized. Using words or images to describe the phenomena of the actions of the existing protagonist and antagonist characters. Characters' actions in passages from Putu Wijaya's